Telepsychiatry of Health Workers For Patient ODGJ Psychogeriatri - Wahyuningsih, S; Dida, S; Setianti, Y; Suminar, J R (Journal of physics. Conference series, 2018)
The purpose of this study is to find out how the telepsychiatry method performed by health workers Mental Hospital Dr Wardjiman Wediodiningrat Lawang Malang East Java Province for patients ODGJ Psikogeriatri in the village Blandit Wonorejo Singosari Malang. Constructivist paradigm, type of qualitative research with single case study approach. Primary data sources are in-depth interviews, observations, while secondary data is from documentation, audio-visual materials. The object of this research is telepsychiatry of health worker for ODGJ psychogeriatri patient, while research subject is psychiatrist, nurse, installation staff of PKRS RSJ and patient. Purposive sampling. Validity: triangulation, member check. The result of this research is there are three stages are Pre Telepsychiatry; Process of Telepsychiatry; and The Final of Telepsychiatry. Verbal Communication between Health workers and Patients, verbal communication is Oral verbal communication, and verbal communication is written. Nonverbal Communication between health workers and Patient are: Kinesik, Paralanguage, Haptik, touch of warmth. Barriers are the Internet Network's up and down facilities; The lack of a common perception; Broken senses. The interaction with psychiatrists, nurses, and patients ODGJ Psychogeriatri has a similarity of meaning, so telepsychiatry is done as a complement is the recovery of the health of ODGJ patients related to distance.